Asymmetry in Intergovernmental Relations: the Case of the State of Autonomies in Spain - Tamboleo García, Rubén (Revista del CLAD Reforma y Democracia, 2021)
The Spanish Constitution of 1978 sought to connect with the Constitution of 1931 regarding the territorial distribution of power. The result of its execution was one of the most decentralized countries in the world as a complex State, as opposed to fully federal composite states. When Title VIII of the Spanish Constitution of 1978 was approved, a new State of Autonomies was born in Spain. At that time nobody thought it could reach the current development in terms of its complexity, nor what it would be like. This article examines the characteristics of the evolution of the system, such as its organizational configuration, the expenditure of public administrations by government units, the number of public employees by government units and their distribution, and the euros per capita of the autonomous communities. Together with the classic and revised concepts in this subject, the aim of this work seeks to draw the map of the asymmetry of intergovernmental relations. It can be seen how the implementation of the new model of autonomous government and administration generates new dynamics that make it a unique model in the world, although it shares similar features with both purely federal countries and countries that have established autonomous principles such as the Spanish one. This type of study is very important to understand the very complex models of multilevel governance and the intricate relationships between the different government units and administrations that often compete with each other and especially develop interdependent relationships, as it can be seen in countries such as Mexico, Bolivia, Argentina, Brazil and Venezuela, among other non-unitary countries. By studying the dynamics, we arrive at the scientific verification of features such as interdependence and asymmetry that highlights problems for the citizens. For example, due to the dynamics of political influence, some sub-national units -as in the case of Spain- become more relevant than others, with the problem of generating inequalities in terms of citizens’ access to public services.